Comparison of Ipomoea and Grass for Checking Erosion on road Embankments - Batra, P.C.; Gill, G.S. (Journal of Soil and Water Conservation, 2022)
The erosion of road embankments poses a serious problem' for road and canal engineers. The banks are continually eroded by rain water and lot of money is spent annually for repairing the rills and gullies caused by it. Some type of vegetation has to be planted to check this erosion and stabilize these embankments. The highway building programme in the last 10 years has intensified the need of a suitable plant cover for these sites. The Soil Conservation Service Plant Technologists have recommended a number of plants for this purpose. Graetz (2) reported that Sericea (Lespedeza cuneata) had become the standard vegetative cover 'for highway slope cuts and gills in North Carolina (U.S.A.). It was however usually slow in providing good protective soil cover. In order to improve this situation he recommended growing of love grass, Bermuda grass and tall fescue in mixture with it He also indicated that Bermuda grass (Cynorion dactylon) made a more desirable cover for dams and 'provided a quick soil hugging cover. Rodgers (5) listed red fescue, tall fescue and Crown vetch as the mainstay in programme of highway-erosion control with vegetation. He said that Soil Conservation Service had enjoyed great saving from the use of Crown vetch (Coron ilia varia, L.) in place of shrubs and vines. Hawk and Shrader (4) and Gran (3) claimed that Crown vetch had gained wide acceptance for slope stabilization and slopes established to Penngift Crown vetch did not erode even when all surface vegetation had been completely removed. Devet and Davis (1) stated that Fescue in combination with ryegrass had been  used on highly erodible road banks with especially good results.